Analisis Penerapan PSAK 1 tentang Penyajian Laporan Keuangan di PT Sinar Mas Agro Resource and Technology Tbk (SMART) - Septyani Putri, Zazilatul Rochma; Susbiyani, Arik; Yulinartati, Dra; Martiana, Nina (BUDGETING : Journal of Business, Management and Accounting, 2024)
Financial statelmelnts arel madel to melelt thel nelelds of most of its ulselrs. Thelrelforel, accoulnting standards arel relqulireld for thel prelparation of thelsel financial statelmelnts. Standards arel intelndeld as gulidellinels for prelparing financial statelmelnts beltweleln companiels to bel morel ulniform. So that's what relselarchelrs ulseld to relselarch thel Implelmelntation of PSAK 1 Rellateld to Prelselntation of Financial Statelmelnts at PT Sinarmas Agro Relsoulrcels and Telchnology Tbk (SMART) to find oult thel application of PSAK amelndmelnt No. 1. for prelselntation of financial statelmelnts. Thel data ulseld in this stuldy arel selcondary data. Thel typel of relselarch ulseld is qulalitativel delscriptivel. PSAK 1 is still in thel form of PSAK 1 belforel thel amelndmelnt, so thelrel arel selvelral telrms that havel not beleln changeld according to thel provisions that apply in PSAK 1 Relgarding thel Prelselntation of Financial Statelmelnts Amelndmelnt. From thel abovel findings, relselarchelrs can concluldel that in thel prelparation of financial statelmelnts for thel 2022 pelriod, PT Sinar Mas Agro Relsoulrcels and Telchnology Tbk has not ulseld thel amelndmelnt of PSAK 1, so thelrel arel selvelral telrms "Significant" that arel still ulseld in its financial statelmelnts, elspelcially in thel relport listeld in thel Notels for its financial statelmelnts. Keywords: Financial Statements, PSAK 1 Amendment.